Perancangan Model Struktur Bangunan Ruko Bertingkat di Lahan Gambut Menggunakan Metode Building Information Modelling - Yenisa Jestin Ganindyatama; Rudi Waluyo; Subrata Aditama Kittie Aidon Uda (Jurnal Basement : Jurnal Teknik Sipil, 2023)
The development of the world of construction in Indonesia has been very rapid, as evidenced by the methodsused in the design process of construction projects. There are several methods in the building design processsuch as the conventional method and the Building Information Modeling method. Using conventional methodsis considered less effective in terms of cost, quality and time, while using the Building Information Modelingmethod is considered effective and efficient because the design process can be carried out at the same time andis mutually integrated between one discipline and another. Multi-storey shophouses on peat land on JalanAdonis Samad, City of Palangka Raya, were redesigned using the Building Information Modeling method. Thepurpose of this study was to model the structure of multi-storey shop houses on peatlands using the BuildingInformation Modeling method. The building information modeling-based design method, in this case, uses theTekla Structure software to model the structure. The data from this study is secondary data in the form ofShopdrawing and Indonesian Loading Regulations SNI 2847:2019. The design results using the BuildingInformation Modeling method produce construction design modeling with additional information and detailedexplanations in the form of 3D models.